EFFECTIVENESS OF MAGNETIC THERAPY IN PATIENTS WITH DUODENAL ULCER ASSOCIATED WITH INTESTINAL DYSBIOSIS - Qodirova Saodat Rakhimjonovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Duodenal ulcer associated with Helicobacter pylori infection remains one of the major clinical problems in contemporary gastroenterology. Long-term eradication therapy and irrational antibiotic administration frequently result in intestinal dysbiosis, leading to disturbances of intestinal microbiocenosis, decreased immune resistance, and deterioration of patients’ quality of life. The present study aimed to evaluate the therapeutic efficacy of magnetic therapy combined with Ganoderma lucidum extract in patients suffering from duodenal ulcer and intestinal dysbiosis. A total of 200 patients were enrolled and divided into three clinical groups receiving standard eradication therapy, eradication therapy combined with magnetic therapy, and complex therapy including magnetic therapy together with Ganoderma lucidum extract. Clinical manifestations, microbiological parameters, immunological indicators, and psychoemotional status were assessed before and after treatment. The findings demonstrated that combined therapy significantly improved intestinal microbiocenosis by increasing bifidobacteria and lactobacilli while reducing pathogenic flora and Candida species. Moreover, magnetic therapy enhanced microcirculation and regenerative processes, whereas Ganoderma lucidum exhibited pronounced immunomodulatory and antioxidant activity. Patients receiving complex therapy showed marked regression of abdominal pain, flatulence, nausea, and diarrhea, accompanied by normalization of psychoemotional status and improvement of overall quality of life. The obtained results confirm that magnetic therapy and Ganoderma lucidum extract represent promising adjunctive methods in the комплекс management of gastroenterological diseases complicated by intestinal dysbiosis.